Development of V-Mart Learning Media to Improve Student Interest and Learning Outcomes - Uswatun Khasanah; Siti Inganah; Octavina Rizky Utami Putri (JINoP (Jurnal Inovasi Pembelajaran), 2025)
This study aims to develop V-Mart learning media based on PowerPoint and Quizizz. It utilised the material of determinants and inverse matrices of order 3x3 which is valid, practical, and effective. Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model was employed. This study involved 97 senior high school students. The instruments were questionnaires validated by media and material experts, and students’ tests. The results show that V-Mart was valid and feasible, with an average percentage of 92.19%. The average practicality from each class was 74.71%, 78.00%, and 75.00%. The effectiveness was visible from the classical completion of learning outcomes for each class, which were 81.25%, 84.38%, and 72.73%. There was an increase in learning outcomes for each class of 19.85%, 32.03%, and 31.49%. It thus can be said that V-Mart is worthy of recommendation as an innovative alternative to improve student learning, and can be further developed in other topics and digital learning platforms.